Alcohol consumption, aldehyde dehydrogenase 2 gene rs671 polymorphism, and psoriasis in Taiwan - Ya-Ching Chang; Lung-An Hsu; Yu-Huei Huang (Wolters Kluwer Medknow Publications, 2022)
Background: Although alcohol use has been determined as a predisposing factor for psoriasis, research findings have been inconsistent. Objectives: This study investigated whether alcohol intake is causally linked to psoriasis. Methods: The presence of rs671 polymorphism in the aldehyde dehydrogenase 2 (ALDH2) gene was investigated in 258 psoriasis patients and 605 healthy controls. The rs671 was employed as an instrumental variable for predicting alcohol use. Mendelian randomization (MR) was utilized to assess the causality between genetically determined alcohol consumption and psoriasis using the two-stage least-square (2SLS) approach. A replication study of MR analysis with inverse-variance weighting (IVW), MR-Egger regression, and weighted median methods was performed using openly accessible alcohol consumption and psoriasis summary statistics from the UK Biobank. Results: Between psoriasis and controls, there were no significant differences in genotype and allele frequencies for the ALDH2 rs671 polymorphism. The G allele of the rs671 was positively linked with alcohol intake. The ALDH2 rs671 genetically determined alcohol intake was not linked to the risk of psoriasis in the 2SLS analysis (β = −0.011, P = 0.960). The MR replication study also found no evidence of genetic propensity to greater alcohol consumption increasing the risk of psoriasis (β = −0.00065, P = 0.6002 in IVW; β = −0.00099, P = 0.6851 in MR-Egger; and β = −0.00181, P = 0.3558 in weighted median analysis). Conclusion: ALDH2 rs671 may not have a role in psoriasis susceptibility in Taiwanese. The MR analysis found no causality between alcohol consumption and psoriasis.